The interrelationship between social support, risk-level and safety interventions following acute assessment of suicidal adolescents : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Social Policy and Social Work at Massey University, Palmerston North, New Zealand - Smith, Deborah Anne (Massey University, 2001)
This project was undertaken largely to address (a) the concern that New Zealand has one of the highest rates of youth suicide in the world, and (b) the limited empirical research available on crisis assessment and intervention for suicidal adolescents in New Zealand. Research on youth suicide has primarily focused upon examining factors which place youth at-risk for suicidal behaviour. Social support was chosen as a variable of interest in this study due to (a) its importance in fostering healthy adolescent development, and (b) its identification as an important factor in increasing risk of suicide, particularly if it is lacking or of a negative nature. The present investigation tested a model comprising three constructs: social support (i.e., negative and positive), assessed risk-level of suicide, and safety interventions (e.g., hospitalisation, respite care). Two studies were conducted: an archival study and a vignette study. For the archival study, a record review was conducted using acute assessment reports from the Child, Adolescent and Family Service (CAFS). Data from 50 attempter files and 50 ideator files were collected in order to establish reliable measures for the vignette study. The vignette study involved administering a vignette-style questionnaire to 23 CAFS clinicians. With the exception of the Children's Global Assessment Scale (CGAS) scores in the attempter group, the interrater reliability was good on all indices for the archival study. The vignette study indicated adequate reliability for risk-level ratings based on the multi-rater kappa. The archival study demonstrated that there were significant interactions between group and risk-level (recoded), group and negative support severity (recoded), group and positive support, and negative support severity and total safety interventions (recoded). The vignette study revealed significant interactions between negative support severity (without or with positive support) and assessed risk-level, negative support severity (without or with positive support) and total safety interventions (recoded), and assessed risk-level and total safety interventions (recoded). Overall, results from this study indicated that: (a) the greater the level of negative support severity, the higher the risk-level; (b) the greater the risk-level, the greater the number of safety interventions implemented; (c) the presence of positive support, in addition to negative support, appeared to result in lower risk-level assessments, and (d) certain risk-levels were indicative of particular safety interventions. Revisions to the social support model were necessary based on the results obtained. For the vignette study, clinicians' responses with respect to the decision-making process for risk-level and safety interventions were also explored using the principles from a grounded theory approach and inductive content analysis. The results indicated that clinicians use a methodical process when assessing risk-level and making safety intervention recommendations. Process models for assessing risk-level and recommending safety interventions are presented in relation to these findings. This study makes several important contributions to the research on youth suicide by: (a) providing evidence for reliable social support concepts - namely, that of negative support, positive support and negative support severity, (b) assessing the relationship that both negative and positive support have with suicide risk-level, (c) examining the relationship between risk-level assessment and specific individual safety recommendations (other than hospitalisation), and (d) providing evidence of a relationship between negative support severity and recommended safety interventions, not previously tested. The implications of these results are discussed in terms of their application to (a) youth suicide treatment and prevention, (b) current or proposed services and procedures for at-risk youth, and (c) future research.
Keywords: Youth suicide; Crisis assessment; Fields of Research::370000 Studies in Human Society::370200 Social Work::370204 Counselling , welfare and community services